2016
DOI: 10.1371/journal.pone.0147172
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution of Ebola Virus Disease at Sub-National Level during the 2014 West Africa Epidemic: Model Scrutiny and Data Meagreness

Abstract: BackgroundThe Ebola outbreak in West Africa has infected at least 27,443 individuals and killed 11,207, based on data until 24 June, 2015, released by the World Health Organization (WHO). This outbreak has been characterised by extensive geographic spread across the affected countries Guinea, Liberia and Sierra Leone, and by localized hotspots within these countries. The rapid recognition and quantitative assessment of localised areas of higher transmission can inform the optimal deployment of public health re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…For instance, prior work has highlighted that the initial, seemingly exponential spread of the 2014-15 Ebola epidemic in West Africa at the national level was in fact a composition of local asynchronous and sub-exponential outbreaks [5,8]. That is, local district or county-level outbreaks of Ebola show spatial asynchrony and follow a slower growth pattern that can be best approximated by polynomial rather than exponential functions during at least 3 consecutive disease generations (Figure 1).…”
Section: Description Of Early Epidemic Growth Profiles Using Phenomentioning
confidence: 99%
“…For instance, prior work has highlighted that the initial, seemingly exponential spread of the 2014-15 Ebola epidemic in West Africa at the national level was in fact a composition of local asynchronous and sub-exponential outbreaks [5,8]. That is, local district or county-level outbreaks of Ebola show spatial asynchrony and follow a slower growth pattern that can be best approximated by polynomial rather than exponential functions during at least 3 consecutive disease generations (Figure 1).…”
Section: Description Of Early Epidemic Growth Profiles Using Phenomentioning
confidence: 99%
“…Contemporaneous analyses of the West African outbreak suggested a pattern of initially sustained transmission in the community, followed by a slow decline in transmission [22][23][24][25].…”
Section: Calibration Of Type 2 Outbreak Scenariomentioning
confidence: 99%
“…For instance, Merler et al [21] developed a model of Ebola within Liberia using an agent-based spatial model in which the country is represented by a grid with varying population densities. In addition, Santermans and coauthors demonstrated that the outbreak is heterogeneous, with transmission rates differing between locales [26]. This lends credence to the approach of modelling the outbreak as a set of connected local-level outbreaks, as opposed to one homogeneous outbreak.…”
Section: Introductionmentioning
confidence: 93%